Reinforced temporalis fascia with conchal cartilage versus exclusive temporalis fascia grafting in type 1 tympanoplasty: a comparative study - Gosavi, Rahul S.; Gosavi, Shishir D.; Bandgar, Digwijay A.; Gupta, Akash D.; Naik, Pradny S.; Narkhede, Kshipra M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Various grafting materials have been used for the repair of a tympanic membrane perforation over the years, with temporalis fascia and conchal cartilage being the most widely used. Our study is an attempt to compare and analyse the use of exclusive temporalis fascia as grafting material against a reinforced graft consisting of temporalis fascia and conchal cartilage. Methods: This is a prospective study of 100 patients having inactive mucosal chronic otitis media with a dry central perforation with moderate conductive hearing loss, undergoing type 1 tympanoplasty using underlay technique. 50% of the subjects were grafted with temporalis fascia alone while a reinforced temporalis fascia graft along with conchal cartilage was used in the remaining 50% of the cases. The results were evaluated at an interval of 24 weeks after surgery on the basis of graft uptake and hearing restoration (closure of air-bone gap <10 dB). Results: Graft uptake in exclusive temporalis fascia grafting was 86% while it was 94% when a reinforced graft was used; the hearing restoration rates in both the groups were 82% and 80% respectively. Conclusions: Reinforced temporalis fascia grafting along with conchal cartilage gives better results than grafting with temporalis fascia alone as regards to graft uptake, while the audiometric results are comparable in both the groups.